Proselytizing Strategy Of The National Amil Zakat Agency (Baznas) In Sambas District - Nazarudin; Firdaus Muhammad; Andi Aderus; Deni Irawan (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2025)
This study aims to determine the da'wah strategy of the National Amil Zakat Agency (BAZNAS) of Sambas Regency in increasing people's awareness of zakat, optimizing the collection, distribution, and utilization of zakat, and implementing zakat as an instrument of poverty alleviation. This research uses a qualitative approach with descriptive method. The research location is in Sambas Regency, Indonesia, with primary data sources obtained through in-depth interviews with BAZNAS officers, Head and Treasurer of UPZ Sub-district, religious leaders, beneficiary village heads, and zakat recipient communities. Secondary data were obtained from BAZNAS documents, activity reports, poverty statistics, and local policies. The results showed that BAZNAS's da'wah strategy in increasing people's awareness involved a da'wah communication approach, religious education programs, and collaboration with religious leaders. Optimizing zakat management is done through community-based zakat campaigns, utilization of information technology, and implementation of social activities to strengthen social networks. In alleviating poverty, BAZNAS implements a zakat economic empowerment program that is proven to have a positive impact on the independence of mustahik. This research implies that the zakat management model of BAZNAS Sambas Regency can be used as a strategic reference for other regions in Indonesia, especially in building public trust, increasing zakat literacy, and encouraging the transformation of society from mustahik to muzakki in a sustainable manner